Entrepreneurial Nursing interventions for the social emancipation of women in recycling - Dirce Stein Backes; Lisiane de Borba Müller; Giovana Batistella de Mello; Mara Regina Teixeira Caino Marchiori; Andreas Büscher; Alacoque Lorenzini Erdmann (SciELO, 2022)
ABSTRACT Objective: To implement and signify entrepreneurial interventions in Nursing, with a view to the social emancipation of women working in an Association of Recyclable Materials. Method: Action-research with an intervention process based on an action alluding to Mother's Day, carried out in a pandemic period, with the participation of 28 women from a Recycling Association. Results: The reflexive thematic analysis, which enabled the systematic recording of ideas, insights and the meanings of the intervention, gave rise to two categories: From apparent isolation to professional reinvention and from invisibility to dignity and the feeling of social equality. Conclusion: The interventions carried out in an Association of Recyclable Materials in a pandemic period provided, for its female workers, a sense of life, survival, dignity and empowerment, when they expected little or nothing. Enabling a social identity for the women of a Recycling Association implies, in short, overcoming linear interventions focused on assistance.